Administration of Micronized Caffeine Using a Novel Oral Delivery Film Results in Rapid Absorption and Electroencephalogram Suppression - Hines, Rochelle M.; Khumnark, Matthew; Macphail, Ben; Hines, Dustin J. (Frontiers in Pharmacology, 2019)
Route of administration is well-known to impact factors ranging from absorption and distribution, up through the subjective effects of active ingredients. Different routes of administration confer specific advantages, such as more rapid absorption resulting from intravenous injection, or increased convenience with oral administration, but a combination of both rapid and convenient delivery is highly desirable. QuickStrip™ was designed as a rapidly dissolving thin film matrix that contains active ingredients, which may be promising for rapid and convenient delivery via the oral mucosa. To assess the delivery of QuickStrip™, we administered the well-characterized active ingredient caffeine to mice and compared QuickStrip™ to standard oral gavage delivery at an equivalent dose of 20 mg kg-1. Using HPLC assessment of serum concentrations of caffeine, we found that QuickStrip™ delivery resulted in higher serum levels of caffeine at 1, 10, and 30 min following administration compared to gavage. QuickStrip™ also produced greater bioavailability compared to gavage, as demonstrated by area under the curve analysis. Caffeine delivered by QuickStrip™ produced robust behavioral activation of locomotion, consistent with gavage caffeine. Electroencephalographic (EEG) assessment of central nervous system effects demonstrated that both gavage and QuickStrip™ caffeine produced suppression of delta and theta, consistent with prior literature on the effects of caffeine. In addition, QuickStrip™ produced a more rapid onset of EEG suppression, supporting the more rapid absorption demonstrated in the serum studies. Collectively, these studies suggest that QuickStrip™ may provide a balance between convenience and rapid onset, offering new options for delivery of therapeutics.